2021
DOI: 10.1002/esp.5268
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of river channel modification in wadeable, lowland rivers: Exploring overdeep rivers in England

Abstract: Many lowland fluvial systems are suspected to possess a morphological legacy from a long history of channel modifications as a consequence of limited energy and sediment supply to facilitate recovery. We explore the extent of such modifications using a regionally extensive dataset of physical habitat surveys compiled by non-specialist surveyors. Representative photographs for each surveyed site were used to quality check channel width, depth and bed grain size information derived from Modular River Physical (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Box and whisker plots (Figure 4) illustrate the median, 25th percentiles (upper and lower bounds of the box), limits beyond which values are considered outliers (the whiskers) and maximum and minimum observations (diamonds) of these three channel dimensions and of the MoRPh width‐to‐bankfull depth ratio. The latter ratio is used rather than the ratio of bankfull width to bankfull depth because the bankfull width often retains long‐term influences of human modification in low‐energy human‐modified English rivers (Gurnell & Downs, 2021). The expected broad upstream to downstream trends can be observed for all four channel dimension variables (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Box and whisker plots (Figure 4) illustrate the median, 25th percentiles (upper and lower bounds of the box), limits beyond which values are considered outliers (the whiskers) and maximum and minimum observations (diamonds) of these three channel dimensions and of the MoRPh width‐to‐bankfull depth ratio. The latter ratio is used rather than the ratio of bankfull width to bankfull depth because the bankfull width often retains long‐term influences of human modification in low‐energy human‐modified English rivers (Gurnell & Downs, 2021). The expected broad upstream to downstream trends can be observed for all four channel dimension variables (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…In river and wetland contexts, many rapid assessment approaches for assessing channel and ecosystem health and/or monitoring restoration efforts have been developed (e.g., Gurnell et al, 2019; Kotze et al, 2019). Application of some of these approaches have included volunteer citizen scientists and have been shown to generate robust data sets (e.g., Gurnell & Downs, 2021), often in a cost‐ and time‐effective manner. In the New Forest for instance, additional field surveys of similar detail to our 1991, 1997 and 2021 surveys could easily be collected by citizen scientists following a brief (1‐day maximum) training course, capturing decadal changes or responses to particular events (e.g., wind storms, floods).…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary baseline reconnaissance walkover revealed that the Brook within the study reach has average bed and bank full widths of approximately 6 and 11 m, respectively, and a gravel-sand bed showing significant superficial silt deposits and negligible physical bed features. The pre-restoration river channel displayed a generally smooth, straightened course; overdeep channel cross profile (see Gurnell & Downs, 2021, for the methodology used to identify legacy channel overdeepening); and the presence of wooden toe board reinforcement along much if its length (e.g., Figure 2a), indicating significant human interventions. Vegetation colonisation and development coupled with some natural morphological adjustments within the high, steep bank profiles emphasise the historic nature of these interventions and some recovery since their imposition.…”
Section: The Study Sitementioning
confidence: 99%